Effects of interaction between cowpea variety and the application of plant powders on Callosobruchus maculatus (Fabricius) (Coleoptera: Chrysomelidae) infestation of stored cowpea seeds - Azeez, Owolabi Moshood; Osipitan, Adebola Adedoyin; Daniel, Isaac Oludayo; Richard Pitan, Olufemi Olutoyin (Annals of Tropical Research, 2020)
An integrated pest management scheme involving seed resistance and the application of powder of Cymbopogon citratus, Alstonia boonei, Hyptis suaveolens, Azadirachta indica, Loranthus braunii and Lycopersicum esculentum as protectant against the seed bettle, Callosobruchus maculatus (Fabricius), was evaluated in the laboratory at ambient temperature (29±3°C) and relative humidity (65±5%). Six resistant cowpea accessions selected from previous studies were treated with the six plant powders at 1.25% w/w in a 6×7 factorial arrangement fitted into a completely randomized design with five replicates. Seed treatment with any of the six plant powders on six accessions resulted in significantly higher adult mortality, lower oviposition rate, adult emergence inhibition, lower seed damage and higher seed germination over the control, Protection ability of the plant powders was influenced by the cowpea accessions used.